ANATOMI BATANG AREN (ARENGA PINNATA MERR.) - Y I Mandang; Nenny S Sudarna (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
The anatomical features of aren stem in relation to its utilization were studied by taking samples from Bogor Re- gency, West Java. The mature stem has 8 to 10 m of clear bole with 30 to 43 cm in diameter. The hard pheripheral region of the stem is only 0.5 to 5.2 cm in thickness or 4 to 20 percent of the .stem volume.The pheripheral region of the stem consists largerly of fibrouascular bundles while the central portion consists mainly bf parenchyma tissues. The frequency of vascular bundles at pheripheral region may reach 139 bundle/sq. cm then gradually decreased to 10 bundles/sq. cm at the center.The fiber dimension vary along and across the stem: length 1618 to 2712 microns, diameter.28 to 52 microns, wallthickness 5 to 24 microns. The Runhell ratio varies from 0. 56 to 13.33.